2011
DOI: 10.3109/00365521.2011.610003
|View full text |Cite
|
Sign up to set email alerts
|

Lynch syndrome screening in newly diagnosed colorectal cancer in general pathology practice: From the revised Bethesda guidelines to a universal approach

Abstract: The revised Bethesda guidelines are inadequate for LS screening when personal and family cancer history is not available to the pathologist, a universal screening paradigm greatly increased the rate of MSI testing and MSI-H CRC detection and CRCs less likely to be screened for LS were those diagnosed in locally excised specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…Even if screening was extended to patients older than 60 years of age, the prevalence of LS might be lower than expected in Japan, compared with a reported prevalence of LS of 0.5-13 % among CRC patients in Western countries [3,10,11]. In Japan, Furukawa et al [12] reported that mutations in MLH1 or MSH2 were identified in 8 These results suggested that the prevalence of LS differs depending on the country, or even the region within the country. Further investigation of the prevalence of LS according to the region will be important.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Even if screening was extended to patients older than 60 years of age, the prevalence of LS might be lower than expected in Japan, compared with a reported prevalence of LS of 0.5-13 % among CRC patients in Western countries [3,10,11]. In Japan, Furukawa et al [12] reported that mutations in MLH1 or MSH2 were identified in 8 These results suggested that the prevalence of LS differs depending on the country, or even the region within the country. Further investigation of the prevalence of LS according to the region will be important.…”
Section: Discussionmentioning
confidence: 76%
“…However, the application of only the rBG criteria is not sufficient for the selection of LS candidates. Several reports [16][17][18] have suggested that the problem with the rBG criteria is that candidates are limited to an age of younger than 50 years. Recent guidelines for LS screening, including the US Multi-Society Task Force on colorectal cancer [19], the ESMO Clinical Practice Guidelines [20], and the National Comprehensive Cancer Network [21], may overcome these problems and select suitable candidates using MSI testing or IHC prior to genetic testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between January 2004 and March 2009, MSI testing was performed on all primary, surgically resected CRCs in patients diagnosed at age less than 50 years, that were right-sided or displayed any MSI-high (MSI-H) histology, as previously described. 8 Any tumor that was MSI-low or MSI-H then underwent IHC. In April 2009, a universal screening approach was implemented, and all resected CRCs were screened either by MSI testing or IHC.…”
Section: Msi and Ihcmentioning
confidence: 99%
“…This was even more so when the personal and family history were not available to the pathologist [22,23].…”
Section: Discussionmentioning
confidence: 87%